Laboratory characterization of obligate carriers of type 3 von Willebrand disease with a potential role for Platelet Function Analyzer (PFA‐200). (5th January 2022) - Geevar, Tulasi; Dave, Rutvi Gautam; Mathews, Nitty Skariah; Kumar, Snehil; Mammen, Joy John; Vijayan, Ramya; Aboobacker, Fouzia N.; Abraham, Aby; Srivastava, Alok; Nair, Sukesh Chandran
Abstract: Introduction: Type 3 von Willebrand disease (VWD) is a rare autosomal recessive disorder characterized by undetectable von Willebrand Antigen (VWF:Ag). Carriers of type 3 VWD carry one null allele and have von Willebrand factor (VWF) at about 50% of normal. The aim of this study was to characterize type 3 VWD carriers and to study the role of Platelet Function Analyzer (PFA‐200) in this cohort. Methods: This was a cross‐sectional study where data were collected from carriers (parents/offspring) of type 3 VWD patients and evaluated with activated partial thromboplastin time, factor VIII, blood group, ristocetin cofactor assay (VWF:RCo), VWF:Ag, and closure time on PFA‐200 with collagen/epinephrine (COL/EPI), and collagen/ADP (COL/ADP). Results: One hundred carriers were included in the study of which 85 were included for PFA‐200 analysis. The mean (SD) of VWF:Ag (IU/ml) and VWF:RCo (IU/ml) was 0.63 (0.24) and 0.61 (0.26), respectively. Among the 100 carriers, based on VWF levels (VWF:Ag and/or VWF:RCo) and bleeding history, there were 7 type 1 VWD, 10 type 2 VWD, 25 borderline VWF (0.30–0.50 IU/ml and no bleeding), and 58 normal VWF (>0.50 IU/ml). PFA‐200 was prolonged in 71% of the carriers, all carriers with type 1 and type 2 VWD phenotype, 80% carriers with borderline VWF, and 59% with normal VWF. COL/EPI was more sensitive than COL/ADP and showed better correlation with VWF parameters than COL/ADP. Conclusion: Carriers of type 3 VWD can have a variable laboratory phenotype. PFA‐200 showed good sensitivity among the carriers at VWF levels <0.50 IU/ml.